Pengaruh Dukungan Spiritual Terhadap Penurunan Tingkat Kecemasan Pada Pasien Pre Operasi Di Ruang Bedah RSUD Depati Bahrin Kabupaten Bangka - Kgs M. Faizal; Kartini Eka Putri (Universitas Malahayati Lampung, 2021)
ABSTRACK: THE EFFECT OF SPIRITUAL SUPPORT ON DECREASING LEVELS OF ANXIETY OF PRE OPERATING PATIENTS IN SURGERY ROOM RSUD DEPATI BAHRIN OF BANGKKA REGENCY HOSPITAL IN 2019 Background : Operation is a potential and actual threat to the integrity of a person who can evoke physiological and psychological stress reactions, and is a difficult experience for almost all patients. Various bad possibilities can occur that will endanger the patient. So do not be surprised if often patients and families show excessive attitude with anxiety experienced. One of the nursing interventions that can be done is spiritually. Based on data from operating patients from the Depati Bahrin Regional Hospital in Bangka Regency, data was obtained in 2016 there were 1.317 patients, in 2017 there were 1.290 patients, data in 2018 there were 1.028 patients operating.Purpose : The purpose of this study was to determine the effect of spiritual support on reducing anxiety levels in preoperative patients in the Depati Bahrin of Bangka Regency Hospital Surgery Room in 2019.Method : The study was conducted using a simple quasi experimental research design with pre-poest intervention. Samples were taken by non probability sampling method, namely 36 respondents divided into two groups, 18 respondents in the intervention group and 18 respondents in the control group. The statistical test analysis used in this study was the independent t-test and dependent t-test or paired t-test.Result : The results showed that there were differences in the level of anxiety obtained p value = 0,000 in the intervention group, while the control group obtained a value of p = 0.210, it can be concluded that there is a significant difference between the level of anxiety before and after the intervention and control groups.Conclusion : Suggestions researchers should hospitals take a policy about the implementation of meeting the spiritual needs of patients preoperatively by involving spiritual teachers. Keywords: Support, Spiritual, Anxiety, Patient, Preoperative INTISARI: PENGARUH DUKUNGAN SPIRITUAL TERHADAP PENURUNAN TINGKAT KECEMASAN PASIEN PRE OPERASI DI RUANG BEDAH RSUD DEPATI BAHRIN KABUPATEN BANGKA Pendahuluan : Tindakan pembedahan merupakan ancaman potensial maupun aktual pada integritas seseorang yang dapat membangkitkan reaksi stress fisiologis maupun psikologis, dan merupakan pengalaman yang sulit bagi hampir semua pasien. Berbagai kemungkinan buruk bisa terjadi yang akan membahayakan bagi pasien. Maka tidak heran jika sering kali pasien dan keluarga menunjukkan sikap yang berlebihan dengan kecemasan yang dialami. Salah satu intervensi keperawatan yang bisa dilakukan adalah dengan spiritual. Berdasarkan data pasien operasi dari RSUD Depati Bahrin Kabupaten Bangka diperoleh data pada tahun 2016 terdapat 1.317 orang pasien, data tahun 2017 tedapat 1.290 orang pasien, data pada tahun 2018 terdapat 1.028 pasien operasi. Tujuan : Untuk mengetahui pengaruh dukungan spiritual terhadap penurunan tingkat kecemasan pada pasien pre operasi di Ruang Bedah RSUD Depati Bahrin Sungailiat Tahun 2019.Metode : Penelitian dilakukan dengan menggunakan desain penelitian quasi eksperiment sederhana dengan pre-poest intervensi. Sampel diambil dengan metode non probability sampling yaitu 36 responden yang terbagi dua kelompok, 18 responden kelompok intervensi dan 18 responden kelompok kontrol. Analisis uji statistik yang digunakan dalam penelitian ini adalah uji Independen t-test dan dependen t-test atau paired t-test.Hasil Penelitian : Hasil penelitian diketahui ada perbedaan tingkat kecemasan didapatkan nilai p = 0,000 pada kelompok intervensi, Sedangkan kelompok kontrol didapatkan nilai p = 0,210 maka dapat disimpulkan bahwa ada perbedaan yang signifikan antara tingkat kecemasan sebelum dan sesudah pada kelompok intervensi dan kontrol.Kesimpulan : Saran peneliti sebaiknya rumah sakit mengambil kebijakan tentang penerapan pemenuhan kebutuhan spirituak pasien pre operasi dengan cara melibatkan guru spiritual. Kata Kunci : Dukungan, Spiritual, Kecemasan, Pasien, Pre Operasi